SUBSTITUSI PARSIAL TEPUNG TERIGU DAN TEPUNG JAGUNG PULUT DENGAN PENAMBAHAN BAKING POWDER PADA PEMBUATAN BISKUIT - Lera, Herkulanus; Ahmadi, KGS; Sasongko, Pramono (Universitas Tribhuwana Tunggadewi, 2018)
Biscuits is one of favorit snack of Indonesian people. It produce from wheat flour which is imported from abroad. Therefore, by this biscuit production pulut corn flour originally from Indonesia can subtitute the wheat flour. The aim of this research is to determined the best composition in partial subtitution of wheat flour and pulut corn flour with addition of baking powder in biscuit production and it feasibility study. This research was conducted in Complete Randomize Block Design factorial with two factors. The first factor is the composition of partial subtitution of wheat flour and pulut corn flour in 4 levels . Second factors is the percentage of baking powder composition (1, 2, and 3%). All factors combinations was run in duplicate with 32 samples obtained. The result of the research was shown thath the best treatment were obtained from substitution 70 % of pulut corn flour and 30% of wheat flour with addition 1% of baking powder. That result shown that the biscuit have 5,87 % of moisture content; 2,07 % of ash; 17,92% of protein, 13,85N of brittleness. Biskuit merupakan salah satu makanan ringan yang digemari oleh masyarakat Indonesia. Biskuit dibuat dengan bahan baku utama tepung terigu yang ketersediaanya masih dicukupi melalui impor. Oleh karena itu melalui pembuatan cookies jagung pulut ini dapat menjadi proses subtitusi tepung terigu dengan tepung jagung pulut asli dari Indonesia. Tujuan dari penelitian ini adalah mendapatkan komposisi terbaik pada substitusi parsial tepung terigu dengan tepung jagung pulut dan penambahan baking powder dalam pembuatan biskuit serta analisa kelayakan usahanya. Penelitian ini menggunakan rancangan acak kelompok ( RAK ) faktorial dengan 2 faktor. Faktor pertama yaitu substitusi parsial tepung terigu dengan tepung jagung pulut, terdiri dari 4 taraf perlakuan. Faktor kedua yaitu komposisi baking powder (1, 2, dan 3%). Seluruh kombinasi diulang sebanyak 2 kali. Hasil penelitian menunjukan bahwa perlakuan terbaik terdapat pada substitusi tepung terigu 70% dengan tepung jagung pulut 30% dan penambahan baking powder 1% dengan parameter kadar air 5,87%, kadar abu 2,07%, protein 17,92%, daya patah 13,85 N.